Case Report: A novel MET exon 14 skipping mutation after EGFR-TKI resistance in advanced lung adenocarcinoma and sustained clinical response to savolitinib - Xue, Yinyin; Li, Wen; Li, Pengfei; Huang, Kaili; Zhou, Qinghua; Wu, Qiang (Frontiers in Pharmacology, 2025)
BackgroundThe MET proto-oncogene (MET) plays a crucial role as an oncogenic driver gene in non-small cell lung cancer (NSCLC). At present, numerous types of MET exon 14 (METex14) skipping mutation have been identified, but different splice variants often exhibit varying treatment responses. There is currently no standardized treatment approach for rare METex14 mutation after resistance to epidermal growth factor receptor tyrosine kinases inhibitor (EGFR-TKI). Herein, we present for the first time a case of advanced lung adenocarcinoma with a novel METex14 skipping mutation following resistance to EGFR-TKI and subsequent sensitivity to savolitinib. In addition, the patient developed a novel METex14 skipping mutation after EGFR-TKI resistance, which we suspect may be a potential new mechanism of EGFR-TKI resistance that has not been reported.Materials and methodsWe conducted surgical specimen pathology diagnosis and next-generation sequencing (NGS) of peripheral blood to ascertain the patient’s pathological and molecular characteristics.ResultsNGS testing identified a novel METex14 (c.2888-23_2888-8del) skipping mutation in the patient with advanced lung adenocarcinoma who developed resistance to EGFR-TKI, suggesting its potential involvement as one of the mechanisms underlying the resistance to EGFR-TKI. Following administration of savolitinib with a daily dose of 400 mg, the patient exhibited a partial response and achieved progression-free survival (PFS) exceeding 8 months.ConclusionThe case presents a novel METex14 skipping mutation that emerges subsequent to the progression of advanced lung adenocarcinoma following EGFR-TKI treatment. Importantly, this mutation may serve as one of the mechanisms contributing to resistance against EGFR-TKI and exhibit sensitivity towards savolitinib treatment, providing reference for future similar cases in terms of treatment options.